DESIGN OF INFORMATION SYSTEM FOR QUALITY MANAGEMENT - Yulius Halim (Jurnal Teknik Industri: Jurnal Keilmuan dan Aplikasi Teknik Industri, 2002)
A quality management recently has been the concepts that using a great mass of information flow. The unique function of information in quality management has become the driver of this study. There is a need of building the model for quality management information system before designing the information system. This paper will show two points that important for the information system. The points, database model and expert system, will be explained as the part of the information system for quality management.